Self-esteem, Motivation, and Emotional Intelligence: Three Factors that influence the Successful Design of a Life Project of Middle-school Young Students - Lomelí-Parga, Andrea Magdalena; López-Padilla, María Guadalupe; Valenzuela-González, Jaime Ricardo (Revista Electrónica Educare, 2016)
The purpose of this research study is to depict the factors that allow young people to effectively carry out their life projects by planning short, mid, and long term goals. The population sample participating in this study was comprised of middle and high school students. This research was executed using mixed methods in order to identify the determining factors for young people who plan to have success in facing the daily life challenges, as well as today’s society demands, through a solid construction of their private vision of the future. The results of this project determine that the features which allow the conclusion of students’ life projects are closely related with a high self-esteem and motivation, as well as some emotional intelligence that allow students to visualize a successful personal and professional future.